KERJASAMA RCEP ( REGIONAL COMPREHENSIVE ECONOMIC PARTNERSIP ) TERHADAP PERDAGANGAN LUAR NEGERI INDONESIA-TIONGKOK TAHUN 2022-2023 - Rahmawati, Suci; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to evaluate the impact of the Regional Comprehensive Economic Partnership (RCEP) cooperation on Indonesia-Tiongkok foreign trade during the period 2022-2023. The main issue examined is how RCEP influences Indonesia-Tiongkok foreign trade from 2020 to 2023. As the world’s largest free trade agreement involving 15 member countries, RCEP is expected to reduce trade barriers and enhance regional economic integration. Based on the theory of regional economic integration, this study focuses on how RCEP, as the world’s largest free trade agreement, functions to reduce trade barriers and improve economic efficiency in the Asia-Pacific region The methodology used is a qualitative descriptive method with secondary data analysis. Data were obtained from international trade reports, export-import statistics, and sesuai t policy documents, which were analyzed to describe the dynamics of Indonesia-Tiongkok trade during the study period. The results indicate that the implementation of RCEP has had a positive impact on Indonesia-Tiongkok trade relations, as evidenced by a significant increase in bilateral trade value, especially in the manufacturing and agricultural sectors. The elimination of tariffs and simplification of trade procedures within the RCEP framework have expanded market access for Indonesian products in Tiongkok. However, challenges such as trade balance imbalances and competition between domestic products and Chinese imports remain. In conclusion, RCEP contributes to strengthening trade relations through increased efficiency and product diversification, but national strategies are needed to improve the competitiveness of local products and address its negative impacts. Keywords: RCEP, Indonesia-Tiongkok, Exports and Imports